Perlindungan Hak Anak dalam Kemajuan sebuah Bangsa - Achmad Zarkasyi Yahya; M Ikhfal Khaqiqi; Mega Dewi Ambarwati (LITERATUS, 2022)
Based on the constitution of the republic of Indonesia in 1945, the rights of the child is protected and followed by local governments that have done and approach to using the friendly city of the child. Indonesia has therefore been taking part in a movement to protect the rights of the child, and is being followed by a community that teaches about child protection.